The Influence of Time Management, Learning Discipline, and Learning Facilities on Students’ Mathematics Learning Outcomes - Rifani Aulia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to see the influence of time management, learning discipline, and learning facilities on student mathematics learning outcomes partially and simultaneously. This type of research is ex-post facto design. The population in this study were tenth and eleventh grade students at SMA Swasta Dharma Pancasila Medan. The number of samples used was 63 students consisting of 34 tenth grade students and 29 eleventh grade students. The data collection method was carried out using questionnaires and documentation. The data analysis technique used is classical assumption test, multiple linear regression test, and hypothesis test. The research results showed that there is influence of time management, learning discipline, and learning facilities on students’ mathematics learning outcomes partially and simultaneously.